2001
DOI: 10.1039/b106766b
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular addition of acyl radicals to α-substituted vinylogous carbonates: demonstrating the effect of ring size on acyclic stereocontrolElectronic supplementary information (ESI) available: spectral data (IR, 1H and 13C NMR) and high resolution MS for 1/2a-c, 7–10. See http://www.rsc.org/suppdata/cc/b1/b106766b/

Abstract: The level of stereocontrol obtained in the reduction of the free radical derived from the intramolecular addition of an acyl radical to an alpha-branched vinylogous carbonate is dependent upon the ring-size of the cyclic ether.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…For instance, while moderate diastereocontrol was observed in the formation of 180 (Scheme 108), higher selectivity was achieved in the formation of the corresponding pyran, while surprisingly five-membered ring formation gave the weakest stereochemical control of all. 218 Diazo-decompositions to give medium-ring ethers have focused mainly on O-H insertion and formation and rearrangement of oxonium ylides. More recently it has been shown that treatment of 181 with copper() hexafluoroacetylacetonate gives 182 chemoselectively.…”
mentioning
confidence: 99%
“…For instance, while moderate diastereocontrol was observed in the formation of 180 (Scheme 108), higher selectivity was achieved in the formation of the corresponding pyran, while surprisingly five-membered ring formation gave the weakest stereochemical control of all. 218 Diazo-decompositions to give medium-ring ethers have focused mainly on O-H insertion and formation and rearrangement of oxonium ylides. More recently it has been shown that treatment of 181 with copper() hexafluoroacetylacetonate gives 182 chemoselectively.…”
mentioning
confidence: 99%